Avaliação comparativa entre a colagem direta e indireta de bráquetes ortodônticos estudo clínico e periodontal randomizado - Zanini, Mauricio Matte (2015)
Objective: This project aimed: a) to evaluate two techniques for bonding brackets, direct and indirect, in relation to the following variables: failures (amount of debonded brackets), type of failure (adhesive or cohesive) and clinical time; b) to validate the accuracy of indirect bonding. Methods: 25 patients were randomized selected, 17 of whom remained in the study (10 men and 7 women) with a mean age of 15,8 years, and these were subjected to comprehensive orthodontic treatment (braces), totaling a sample size of 260 teeth examined. A "split-mouth" experimental design was used, for each patient the brackets were bonded in the superior hemiarch through direct technical and other indirectly, the same occurring in the lower arch. Assessments occurred in the following periods: pre-bonding, one, three and six months after the initial placement of the brackets. Data were statistically analyzed sing Fisher and Chi-square test for the number and the type of failure, t test for comparison of the change in bracket position between the working model and patient´s model, and the bonding time between the different techniques. Results: The indirect technique presented a higher number of debonding brackets and more adhesive failures in comparison with the direct technique (p<0.05).The clinical procedure of indirect bonding was faster than the direct bonding (p<0.05). The accuracy of the brackets placement showed statistically significant differences (p<0.05). As for the angular measurements, there was no statistically significant difference (p>0.05). Conclusions: The indirect technique has statistic superiority with less clinical time, but should be expected more brackets debonding during treatment, and changes in the positioning of brackets on patients teeth.